Gravitactic orientation of Euglena gracilis—a sensitive endpoint for ecotoxicological assessment of water pollutants - Ullah, Aziz; Murad, Waheed; Adnan, Muhammad; Ullah, Waheed; Häder, Donat P. (Frontiers in Environmental Science, 2013)
Pollution of aquatic environments with natural and anthropogenically produced substances is one of the major environmental problems of the world. In many countries the decreasing quantity of water coupled with its increasing usage in multiple sectors has adversely affected water quality and caused problems of water pollution. Polluted water has been a main cause of adverse effects on plants, animals and humans throughout the world. Physicochemical analysis of water, which is a common method used for quality assessment of water, alone may not be enough as it cannot evaluate the impact on living organisms. Therefore, bioassessment of water and wastewater quality is considered to be essential to reflect the ultimate effects on living organisms. Many organisms like bacteria, algae, fish, invertebrates and protozoan are used as bioassay organisms for assessment of water quality. This review article elucidates the use of Euglena gracilis, a freshwater motile flagellate of the phylum Euglenophyta, as a suitable organism in ecotoxicological studies with special emphasis on its gravitactic orientation as a sensitive end point in ecotoxicological assessment of water pollutants.